2008
DOI: 10.1016/j.jcmg.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hand-Carried Ultrasound Assessment of the Inferior Vena Cava and N-Terminal Pro-Brain Natriuretic Peptide for Predicting Readmission After Hospitalization for Acute Decompensated Heart Failure

Abstract: This study confirms that, once hospitalized, patients with CHF frequently are readmitted. Bedside evaluation of the IVC with a HCU device at the time of admission and discharge, as well as pre-discharge BNP, identified patients admitted with ADHF who were more likely to be readmitted to the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
109
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(120 citation statements)
references
References 25 publications
9
109
2
Order By: Relevance
“…Studies include evaluations of clinical parameters such as angina, low systolic blood pressure, edema levels, elevated jugular venous pressure, age, depressive symptoms, and the presence of coronary heart disease and pacemakers 13. Serum biomarkers have received the most attention, as simple objective measurements that can be and are routinely performed at admission, such as BNP,14, 15, 16 blood urea nitrogen,17, 18 hemoglobin and hematocrit,19 cystatin,15 and cardiac troponin 15. Hemodynamic predictors have also been evaluated to more specifically determine volume status to prevent premature hospital discharges and to reduce readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies include evaluations of clinical parameters such as angina, low systolic blood pressure, edema levels, elevated jugular venous pressure, age, depressive symptoms, and the presence of coronary heart disease and pacemakers 13. Serum biomarkers have received the most attention, as simple objective measurements that can be and are routinely performed at admission, such as BNP,14, 15, 16 blood urea nitrogen,17, 18 hemoglobin and hematocrit,19 cystatin,15 and cardiac troponin 15. Hemodynamic predictors have also been evaluated to more specifically determine volume status to prevent premature hospital discharges and to reduce readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the concept of impedance, which correlates to pulmonary artery wedge pressures, as measured by cardiac resynchronization therapy defibrillator devices, has shown promise but requires an implanted device 24. Simpler bedside ultrasound devices have been used to measure hepatic venous flow25 and inferior vena cava collapsibility index16, 26, 27 as measures of RAP and central venous pressure, respectively. Ultimately, no technique has emerged as a validated and reproducible predictor of early 30‐day readmission following treatment for ADHF.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited number of primary outcome events, we used age, IVC diameter, and log NT-proBNP in the multivariate regression analysis based on past studies showing prognostic significance of these variables. 6,[22][23][24][25][26][27][28] Optimal cutoff values for IVC diameter for death and readmission prediction were determined by constructing receiver operating characteristic (ROC) curves and calculating the area under the curve (AUC) for different IVC diameters. NT-proBNP values were log-transformed to minimize skewing as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,37 Goonewardena et al showed a 41.3% readmission rate at 30 days in patients with severely reduced left ventricular ejection fraction (mean 29%), and readmitted patients had an IVC max diameter >2 cm and an IVC collapsibility <50% on admission and discharge. 6 Carbone et al demonstrated absence of improvement in the minimum IVC diameter from admission to discharge using hand-carried ultrasound in patients with ischemic heart disease (ejection fraction 33%) predicted readmission at 60 days. 38 Hospital readmission rates in our study are consistent with these previously published studies.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation